Pengaruh Permintaan e-Money terhadap Pendapatan per Kapita di Indonesia - Mohamad Ghozali; Triaji Pambudi (Al-Amwal : Jurnal Ekonomi dan Perbankan Syari'ah, 2018)
This research aims to analyze the effect of e-money demand on per capita income in the long and short term in Indonesia. This research method is quantitative descriptive. This research was conducted with secondary data and observation time in 2013: Q1 - 2017: Q4. Data was obtained from Bank Indonesia publication data and the Indonesian Central Statistics Agency (BPS). Data analysis techniques using Error Correction Model (ECM). The results of the analysis show that in the long run per capita income has a positive and significant effect on e-money demand. In the short term, per capita income has a positive and insignificant effect on e-money demand. The implication of the conclusions above is that first, the government needs to disseminate the Non-Cash Direct Aid program so that all people begin to recognize non-cash instruments. Secondly, Bank Indonesia needs to pay attention to the interconnection system of the reader machine and pay attention to the amount of currency circulating in order to realize a less cash society.